2010
DOI: 10.1111/j.1460-9568.2010.07406.x
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala, deep cerebellar nuclei and red nucleus contribute to delay eyeblink conditioning in C57BL /6 mice

Abstract: That the cerebellum plays an essential role in delay eyeblink conditioning is well established in the rabbit, but not in the mouse. To elucidate the critical brain structures involved in delay eyeblink conditioning in mice, we examined the roles of the deep cerebellar nuclei (DCN), the amygdala and the red nucleus (RN) through the use of electrolytic lesions and reversible inactivation. All mice received eyeblink training of 50 trials during a daily session in the higher-intensity conditioned stimulus (CS) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 53 publications
4
29
2
Order By: Relevance
“…(2) We have used a very mild air-puff because it has been suggested recently that the much stronger periorbital stimulation typically employed for eyeblink conditioning in mice leads to a fear-related blink with a relatively fixed short-latency (Boele et al, 2010), and there is indirect evidence that in some cases this short-latency response can interfere with the adaptively timed component of the conditioned eyelid response (Aiba et al, 1994; Sakamoto and Endo, 2011). (3) We have developed a system that allows mice to be conditioned while they are actively engaged in one of their favorite activities: treadmill walking.…”
Section: Discussionmentioning
confidence: 99%
“…(2) We have used a very mild air-puff because it has been suggested recently that the much stronger periorbital stimulation typically employed for eyeblink conditioning in mice leads to a fear-related blink with a relatively fixed short-latency (Boele et al, 2010), and there is indirect evidence that in some cases this short-latency response can interfere with the adaptively timed component of the conditioned eyelid response (Aiba et al, 1994; Sakamoto and Endo, 2011). (3) We have developed a system that allows mice to be conditioned while they are actively engaged in one of their favorite activities: treadmill walking.…”
Section: Discussionmentioning
confidence: 99%
“…Amygdala lesions significantly slow the rate of CR acquisition depending on the conditioning parameters (Weisz et al 1992). However, damage of the amygdala reduces the asymptotic level of learning (Blankenship et al 2005; Sakamoto and Endo 2010), as it likely reduces the appreciation of the US (Christian and Thompson 2003; Whalen and Kapp 1991). This is a different pattern than obtained in the present study where intraseptal GAT1-SAP eventually reached the same level of performance, as sham-lesioned animals, during the second session.…”
Section: Discussionmentioning
confidence: 99%
“…However, genetically modified mice with altered cerebellar functions constantly result in the incomplete loss of conditioned responses (CR) during delay eyeblink conditioning [9][14]. Furthermore, lesions or inactivation of deep cerebellar nuclei (DCN) did not impair the acquisition and expression of delay eyeblink conditioning [12], [15]. We revealed that mouse DCN play important roles in delay eyeblink conditioning with the low intensity CS [16], but not with high intensity CS [15].…”
Section: Introductionmentioning
confidence: 85%